Relation of the Allelic Variants of Multidrug Resistance Gene to Agranulocytosis Associated With Clozapine. Issue 3 (June 2016) - Anil Yağcioğlu, A. Elif; Yoca, Gökhan; Ayhan, Yavuz; Karaca, R. Özgür; Çevik, Lokman; Müderrisoğlu, Ahmet; Göktaş, Mustafa T.; Eni, Nurhayat; Yazici, M. Kâzim; Bozkurt, Atilla; Babaoğlu, Melih O.
Abstract : Abstract: Clozapine use is associated with leukopenia and more rarely agranulocytosis, which may be lethal. The drug and its metabolites are proposed to interact with the multidrug resistance transporter (ABCB1/MDR1) gene product, P-glycoprotein (P-gp). Among various P-glycoprotein genetic polymorphisms, nucleotide changes in exons 26 (C3435T), 21 (G2677T), and 12 (C1236T) have been implicated for changes in pharmacokinetics and pharmacodynamics of many substrate drugs. In this study, we aimed to investigate the association between these specific ABCB1 polymorphisms and clozapine-associated agranulocytosis (CAA). Ten patients with a history of CAA and 91 control patients without a history of CAA, despite 10 years of continuous clozapine use, were included. Patient recruitment and blood sample collection were conducted at the Hacettepe University Faculty of Medicine, Department of Psychiatry, in collaboration with the members of the Schizophrenia and Other Psychotic Disorders Section of the Psychiatric Association of Turkey, working in various psychiatry clinics. After DNA extraction from peripheral blood lymphocytes, genotyping was performed using polymerase chain reaction and endonuclease digestion. Patients with CAA had shorter duration of clozapine use but did not show any significant difference in other clinical, sociodemographic characteristics and in genotypic or allelic distributions of ABCB1 variants and haplotypes compared with control patients. Among the 10 patients with CAA, none carried the ABCB1 all-variant haplotype (TT-TT-TT), whereas the frequency of this haplotype was approximately 12% among the controls. Larger sample size studies and thorough genetic analyses may reveal both genetic risk and protective factors for this serious adverse event.